An Health Education to Prevent Hypertension in Kampung Pulo, East Jakarta: Edukasi Kesehatan Pencegahan Hipertensi Di Kampung Pulo Jakarta Timur - Hidhayanti, Hayyu Naafi; Mubarak, Fahrul; Syahrani, Destiana; Sima, Razita; Indriani, Sri (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2024)
Hypertension is a health problem in all regions of the world and a major risk factor for cardiovascular disease. Hypertension is also known as a non-communicable disease because high blood pressure is not contagious from person to person. The purpose of education is to educate residents of Kampung Pulo about hypertension. This education was held on April 17, 2023. The number of targets for this education was 25 residents, with specific data for 22 women and 3 men. This education uses the knowledge method by explaining the meaning, signs, and symptoms of factors, prevention, foods that are safe for consumption, as well as examples of drugs regarding hypertension, then the attitude method by distributing posters containing hypertension, and finally the skill method by measuring blood pressure to residents of Kampung Pulo. Before being given education, it showed that 45% did not know, while after being given education, 55% of the people already understand.